Identification of preserved egg white protein glycation and insight into the bioactivity. (6th June 2022) - Wang, Chenyan; Meng, Yaqi; Ning, Qiu; Guyonnet, Vincent; Keast, Russell; Zhu, Chunxia; Mine, Yoshinori
Abstract: Preserved eggs have been reported to possess anti‐inflammatory and antioxidant bioactivities, which are enhanced after protein glycation. However, it is still unknown which proteins are glycated during pickling process of preserved eggs and whether the glycated proteins are related to the bioactivity of preserved eggs. In this study, UPLC‐ESI‐MS/MS was used to identify glycation of proteins in preserved egg white (PEW) and duck egg white (DEW). Altogether, 142 sites on 53 glycated proteins were detected in PEW while 9 sites on 2 glycated proteins were found in DEW. Bioinformatic analysis suggested that the glycation of PEW proteins (e.g. Ovalbumin, Ovotransferrin, Albumin) were supposed to be connected with allergenicity reduction, and the enhancement of antibacterial and antioxidant bioactivities. These findings provide some indications for the future studies on the detailed bioactivities of glycated proteins in PEW, and pave the way for applied research on glycation and the development of functional foods. Abstract : Experimental flow diagram for the identification of preserved egg white protein glycation.